In vitro antioxidant activity and a-amylase inhibitory activity of ethanol extract and fraction of Ganoderma lucidum - Danang Raharjo; Fatimah Azzahro (The International Science of Health Journal, 2025)
The objective of this study is to determine the antioxidant and antidiabetic potential of ethanol extracts and fractions of Ganoderma lucidum. G. lucidum has been traditionally used for its medicinal properties, and recent studies suggest it may possess significant bioactive compounds with therapeutic potential.